Membrane-Active Hydantoin Derivatives as Antibiotic Agents - Su, Ma (J Med Chem, 2017)
Hydantoin (imidazolidinedione) derivatives such as nitrofurantoin are small molecules that have aroused considerable interest recently due to their low rate of bacterial resistance. However, their moderate antimicrobial activity may hamper their application combating antibiotic resistance in the long run. Herein, we report the design of bacterial membrane-active hydantoin derivatives, from which we identified compounds that show much more potent antimicrobial activity than nitrofurantoin against a panel of clinically relevant Gram-positive and Gram-negative bacterial strains. These compounds are able to act on bacterial membranes, analogous to natural host-defense peptides. Additionally, these hydantoin compounds not only kill bacterial pathogens rapidly but also prevent the development of methicillin-resistant Staphylococcus aureus (MRSA) bacterial resistance under the tested conditions. More intriguingly, the lead compound exhibited in vivo efficacy that is much superior to vancomycin by eradicating bacteria and suppressing inflammation caused by MRSA-induced pneumonia in a rat model, demonstrating its promising therapeutic potential.